Estimation of Bait Uptake by Badgers, Using Non-invasive Methods, in the Perspective of Oral Vaccination Against Bovine Tuberculosis in a French Infected Area - Payne, Ariane; Ruette, Sandrine; Jacquier, Mickaël; Richomme, Céline; Lesellier, Sandrine; Middleton, Sonya; Duhayer, Jeanne; Rossi, Sophie (Frontiers in Veterinary Science, 2022)
Although France is officially declared free of bovine tuberculosis (TB), Mycobacterium bovis infection is still observed in several regions in cattle and wildlife, including badgers (Meles meles). In this context, vaccinating badgers should be considered as a promising strategy for the reduction in M. bovis transmission between badgers and other species, and cattle in particular. An oral vaccine consisting of live BCG contained in bait is currently under development for badgers, for which testing bait deployment in the field and assessing bait uptake by badgers are required. This study aimed to evaluate the bait uptake by badgers and determine the main factors influencing uptake in a TB infected area in Burgundy, north-eastern France. The baits were delivered at 15 different setts located in the vicinity of 13 pastures within a TB infected area, which has been subject to intense badger culling over the last decade. Pre-baits followed by baits containing a biomarker (Rhodamine B; no BCG vaccine) were delivered down sett entrances in the spring and summer of 2018. The consumption of the marked baits was assessed by detecting fluorescence, produced by Rhodamine B, in hair collected in hair traps positioned at the setts and on the margins of the targeted pastures. Collected hairs were also genotyped to differentiate individuals using 24 microsatellites markers and 1 sex marker. Bait uptake was estimated as the proportion of badgers consuming baits marked by the biomarker over all the sampled animals (individual level), per badger social group and per targeted pasture. We found a bait uptake of 52.4% at the individual level and a mean of 48.9% and 50.6% at the social group and pasture levels respectively. The bait uptake was positively associated with the presence of cubs (social group level) and negatively influenced by the intensity of previous trapping (social group and pasture levels). This study is the first conducted in France on bait deployment in a badger population of intermediate density after several years of intensive culling. The results are expected to provide valuable information towards a realistic deployment of oral vaccine baits to control TB in badger populations.